2014
DOI: 10.4067/s0718-95162014005000036
|View full text |Cite
|
Sign up to set email alerts
|

Using agronomic biofortification to boost zinc, selenium, and iodine concentrations of food crops grown on the loess plateau in China

et al.

Abstract: Micronutrient malnutrition among humans is typically caused by micronutrient deficiency in soils and then staple food crops grown on these soils. In this study, field trials were conducted to investigate the biofortification of micronutrients in the edible parts of winter wheat, maize, soybean, potato, canola, and cabbage. Fertilizers of Se, Zn and I were applied to soil independently or together, while Se and Zn were sprayed as solution on winter wheat in another part of the trials. Selenium, when applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 26 publications
5
72
0
4
Order By: Relevance
“…There have been some comprehensive studies on the interactions between Se and I in plant uptake processes, as well as on their distribution within plants and their selected chemical properties in plants. 10,[17][18][19] However, there has been little consideration of the interactions between various chemical forms of Se and I, in terms of their effects on the physiological and biochemical characteristics of the plants. 8,20,21 More recently, common buckwheat has become an increasingly important and promising alternative crop because it can be cultivated across a wide range of growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some comprehensive studies on the interactions between Se and I in plant uptake processes, as well as on their distribution within plants and their selected chemical properties in plants. 10,[17][18][19] However, there has been little consideration of the interactions between various chemical forms of Se and I, in terms of their effects on the physiological and biochemical characteristics of the plants. 8,20,21 More recently, common buckwheat has become an increasingly important and promising alternative crop because it can be cultivated across a wide range of growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Agronomic biofortification define the process of increase the concentration of essential elements in portions of plants through fertilization. This strategy was developed as a food-based method to help to decrease widespread deficiencies in Fe and Zn that is prevalent in developing countries (Mao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Micronutrient malnutrition is a major human health problem in the developing world (Yang et al, 2007;Khan et al, 2010;Farooq et al, 2012); however, biofortification offers an attractive and economical solution of this important issue (Mao et al, 2014). Increase in kernel B contents by foliage application of B indicated that, other than breeding efforts, foliage application of micronutrients is also a pragmatic option (Table 5).…”
Section: Discussionmentioning
confidence: 99%